Computational Electromagnetics and Model-Based Inversion A Modern Paradigm for Eddy-Current Nondestructive Evaluation - Sabbagh, Harold A.; Murphy, R. Kim.; Sabbagh, Elias H.; Aldrin, John C.; Knopp, Jeremy S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Computational Electromagnetics and Model-Based Inversion: A Modern Paradigm for Eddy Current Nondestructive Evaluation describes the natural marriage of the computer to eddy-current NDE. Three distinct topics are emphasized in the book: (a) fundamental mathematical principles of volume-integral equations as a subset of computational electromagnetics, (b) mathematical algorithms applied to signal-processing and inverse scattering problems, and (c) applications of these two topics to problems in which real and model data are used. By showing how mathematics and the computer can solve problems more effectively than current analog practices, this book defines the modern technology of eddy-current NDE. This book will be useful to advanced students and practitioners in the fields of computational electromagnetics, electromagnetic inverse-scattering theory, nondestructive evaluation, materials evaluation and biomedical imaging. Users of eddy-current NDE technology in industries as varied as nuclear power, aerospace, materials characterization and biomedical imaging will find this book to be a valuable resource as well.
Preface -- Part I Computational Electromagnetics Background -- 1 Overview of Methods of Computational Electromagnetics -- 2 Green$1 (Bs Dyad for Plane-Layered Media -- 3 The Volume-Integral Equations for Plane-Layered Media -- 4 Discretization via the Galerkin Method of Moments -- 5 Computing Network Immittance Functions from Field Calculations -- 6 Advanced Probe Models Based on Magnetic Dipoles and Ferrite Cores -- 7 Advanced Probe Models Based on Electric Dipoles -- 8 Planar and Conforming Arrays of Probes -- 9 Multilayered Media with Cylindrical Geometries -- 10 Some Special Topics in Computational Electromagnetics -- Part II Inversion Algorithms and Signal-Processing -- 11 Examples of Basic Inverse Problems -- 12 NLSE: Parameter-Based Inversion Algorithm -- 13 Robust Statistical Estimators -- 14 Some Special Signal-Processing Algorithms -- 15 Preprocessing Data and Transformation of Signal Vectors -- Part III Applications -- 16 Modeling Corrosion and Pitting Problems -- 17 Applications to Aerospace Structures -- 18 Applications to Nuclear Power -- 19 Coupled Problems in Heat-Exchanger Tubes -- 20 Applications to NDE of Coatings -- 21 Model-Assisted Probability of Detection -- References -- Index.s
Keywords: System safety; Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Quality Control, Reliability, Safety and Risk; Measurement Science and Instrumentation; Numerical and Computational Physics